Assessment of Knowledge, Attitude, and Practice of HIV Positive Mothers on Antiretroviral Treatment towards Infant Feeding in Gondar Town Health Institutions, North West Ethiopia, 2017 - Daniale Tekelia Ekubagewargies; Habtamu Sewunet Mekonnen; Tsehayu Melak Siyoum (Hindawi Limited, 2019)
Introduction. The world health organization recommends feeding practices for infants born from Human Immunodeficiency Virus infected mothers to be safe to both the infant and the mother. This includes prevention of mother to child transmission of the virus and at the same time meeting nutritional requirements of the child. This requires prioritizing prevention of HIV transmission through breastfeeding against non-HIV morbidity and mortality especially from malnutrition and serious illnesses such as diarrhea, among nonbreastfed infants. Objective. This study was aimed at assessing knowledge, attitude, and practice of HIV positive mothers on antiretroviral therapy towards infant feeding. Method. Institution based cross-sectional study was conducted among 402 HIV positive mothers at ART clinics of Gondar town from March 1 to April 18, 2017. Systematic random sampling technique was used to select study participants. Data was collected using a structured, pretested, interviewer-administered questionnaire. The collected data was entered into Epi Info version 7 and analyzed using SPSS version 20 software. Result. A total of 402 participants were interviewed with a 100% response rate. The mean age of participants was 29.24 (SD±10.06) years. The overall level of participant good knowledge and favorable attitude was 68.91% and 75.87%, respectively. Only 23.7% of mothers were practicing infant feeding according to WHO recommendation.